,,Hromadiws’kij” socjalizm Mychajły Drahomanowa : wizja społeczeństwa bezpaństwa czy państwa bez przymusu? - Jędrysiak, Marcin (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2017)
The goal of this article is to analyze the idea of ,,Hromada’s socialism” invented by the Ukrainian political thinker, Mykhailo Drahomanov. Author wants to answer the question, whether Drahomanov’s idea was an anarchist one – and supported the idea of organizing the society without the state, or was it the ideology that could function inside of state. Basic concepts of Drahomanov’s political thought were presented, as well as his brief biography and ideological inspirations. Author took also into account the very specific, Ukrainian liberalism, which integrated in itself the anarchistic, liberal and socialistic ideas. Author analized the most important political works by Drahomanov: program of the perodical ,,Hromada” (which was also the first Ukrainian political programme), so called ,,Free Alliance”, which was a proposition of transforming Russia into the democratic state. Also, less imposing works were taken into consideration. Basing on this material, the author attempted to identify main issues connected with Hromada’s socialism. That led to the possibility of defining the role of state, form of society and the use of coercion in the society
Keywords: Ukraina; socjalizm; liberalizm; Dragomanov, Mihajlo Petrovič (1841-1895); anarchizm